Answer:
A = 120°
Explanation:
We can use the cosine rule to solve for angle A, since lengths of all sides are known:
![a^2 = b^2+ c^2 - 2(b)(c) \space\ cos A](https://img.qammunity.org/2023/formulas/mathematics/college/6chg7a3xgeltbfzrzhgxpb0w01x4st9sr2.png)
where a, b, and c are the sides opposites angles A, B, and C respectively.
∴ a = 2√3 , b = 6, c = 2
• Rearranging the formula to make A the subject:
![2(b)(c) \space\ cos A = b^2 + c^2 -a^2](https://img.qammunity.org/2023/formulas/mathematics/college/dkg8ak8ua1mjdy3fo3fu26wysa5z6a0poi.png)
⇒
![cos A = (b^2 + c^2 -a^2)/(2(b)(c))](https://img.qammunity.org/2023/formulas/mathematics/college/flw7z5ybcks67lj3oiofqxjx9zxsdt4m6i.png)
⇒
![A = cos^(-1)((b^2 + c^2 -a^2)/(2(b)(c)) )](https://img.qammunity.org/2023/formulas/mathematics/college/ifdzh1bgg6n9zizlv5l81b2rlhg2c01yfq.png)
• Now we can substitute the values into the equation to calculate the value of angle A:
![A = cos^(-1)((6^2 + 2^2 -(2√(13))^2)/(2(6)(2)) )](https://img.qammunity.org/2023/formulas/mathematics/college/1taz0lr3dwz66a3aksncjoivh85zuvqeur.png)
⇒
![A = cos^(-1) (-(1)/(2) )](https://img.qammunity.org/2023/formulas/mathematics/college/9mrwgbxaiqgsgxrecigk0t6g7au50lskvz.png)
⇒ A = 120°